Dust density distribution and imaging analysis of different ice lines in protoplanetary disks - Pinilla, Paola; Pohl, Adriana (The astrophysical journal, 2017)
Recent high angular resolution observations of protoplanetary disks at different wavelengths have revealed several kinds of structures, including multiple bright and dark rings. Embedded planets are the most used explanation for such structures, but there are alternative models capable of shaping the dust in rings as it has been observed. We assume a disk around a Herbig star and investigate the effect that ice lines have on the dust evolution, following the growth, fragmentation, and dynamics of multiple dust size particles, covering from 1 μ m to 2 m sized objects. We use simplified prescriptions of the fragmentation velocity threshold, which is assumed to change radially at the location of one, two, or three ice lines. We assume changes at the radial location of main volatiles, specifically H 2 O, CO 2 , and NH 3 . Radiative transfer calculations are done using the resulting dust density distributions in order to compare with current multiwavelength observations. We find that the structures in the dust density profiles and radial intensities at different wavelengths strongly depend on the disk viscosity. A clear gap of emission can be formed between ice lines and be surrounded by ring-like structures, in particular between the H 2 O and CO 2 (or CO). The gaps are expected to be shallower and narrower at millimeter emission than at near-infrared, opposite to model predictions of particle trapping. In our models, the total gas surface density is not expected to show strong variations, in contrast to other gap-forming scenarios such as embedded giant planets or radial variations of the disk viscosity.
Gesehen am 11.10.2018